An Analysis of Students’ Anxiety in Reading - Ering, Stevanny C.; Pelenkahu, Noldy; Liando, Nihta V. F (Program Studi Pendidikan Bahasa Inggris, 2024)
Language is vital in human existence to mingle. Language is also one of the things that sets humans apart from other animals. This study uses research with a descriptive qualitative approach. According Lexy. J. Moleong, a qualitative approach is a research procedure that produces descriptive data in the form of written or spoken words from people and observed behavior (Saleh, 2021). Based on the research findings, the researcher found that the students have feeling of anxiety. There are three factors that cause students' anxiety in reading when practicing reading in the classroom. Some of the participants answered that they were very worried about having to read in front of the class. They often replied that they started to worry when their teacher asked them to read English text in front of the class.The first factor that causes students to feel anxious is feeling intimidated by the classmate. They are afraid that the classmate will judge them negatively. Limited vocabulary, wrong pronunciation.The second factor is that they feel the material is difficult/English is a difficult subject. They often think that they cannot read properly or understand the lesson. This opinion causes obstacles for students to understand the lesson as a whole. The last factor that contributes to making students feel anxious is don’t know how to pronounce the vocabulary. Students cannot be understand the material because they don’t know how to pronounce and limited vocabulary is the main factor.